Genetic diversity and mating system analysis of Cedrela odorata L. (Meliaceae) populations under different human dominated landscapes and primary forests - Hernández Sánchez, L.G. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) -- CATIE, 2008